(NdWA KAPITANA(B:s (NrOMANs - (NkAWERIN w(B.s ((NmOSKWA(B:s (Nast(B,s, 2005)
"(NdWA KAPITANA(B" - (NZNAMENITYJ ROMAN w(B. (NkAWERINA OB ISSLEDOWATELQH(B-(NPUTE[ESTWENNIKAH(B, (NWOSPEWA@]IJ ROMANTIKU NAU^NOGO POISKA(B.s
(NtIRAV(B: 4000 (N\KZ(B.s
(NiNW(B.: 41679s